Anaerobic degradation of crude oil by sulphate reducing bacteria isolated from soils contaminated with petroleum hydrocarbons - Abd Burghal Al- Asadi, Ahmad (University of Thi-Qar Journal of Science, 2011)
This study included isolatation a mix cultures of sulphate reducingbacteria from soils in Shaeba regain contaminated with petroleum hydrocarbons by using API medium enriched with oxygen reducing agents and saturated with gas (90% N2 ) and( 10% CO2 ) by using sodium lactate as sole carbon source. The result showed that the number of bacteria ranged ( 4 x 105 – 4.5 x 105 ) cells / g of soil. Also using crude oil as a sole of carbon source to study the ability of sulphate reducing bacteria on degradation of crude oil under anaerobic condition . The result showed these bacteria have high ability for degradation of crude oil. The percent rate of degradation in culture was ( 84.4 % ) after (54) days incubation and the rate concentration of total petroleum hydrocarbons ( TPH )extraction from culture value ( 22.06 ) μg / L , while in control was ( 190.84 ) μg / L.